Ozone application in microalgae cultivation effluent to recycle water and nutrients - Santos, Raquel Rodrigues (2019)
Microalgae are microorganisms with high photosynthetic efficiency and capacity of production of oil and biomass far superior to any vascular plant. The production of biodiesel from microalgae still presents limitations to become an economically viable process, such as the high consumption of water and nutrients. Alternatively, ozone gas can be used, as a disinfection agent, which can make possible the reuse of water and nutrients of crops. Ozone has a high potential for oxidation, so it has been used in water and effluent treatment processes. Its high oxidative potential allows the conversion of some organic compounds, non-assimilable by microalgae or even toxic, into nutrients, such as organic acids and amino acids. The objective of this research was to investigate if the treatment with the ozone gas is able to make possible the reuse of water and also nutrients of the crops. For such, a review was first made on the reaction mechanisms of the ozone gas and the culture medium of microalgae. Afterwards, treatments with the following microalgae lineages were carried out: Chlorella sp. BR001, Scenedesmus sp. BR003 and Chlamydomonas sp. CC503, in which the culture supernatant was ozonized, with and without the presence of defatted biomass, to evaluate its effect on water, nutrients and organic compounds. The ozonation was able to discolor the supernatant, which indicates the possibility of its reuse since it improves the penetration of the light for the autotrophic cultures. The analysis of the nutrients showed that there was a significant increase in phosphorus and nitrogen, with the defatted biomass. Variations in carbohydrate and total soluble amino acid concentrations demonstrated that there was a significant increase for both ozone treatments, whether or not the free lipid biomass was added, suggesting that the ozone generated carbohydrates and soluble amino acids from stored carbohydrates and proteins of the cell. To verify the observed results, a new experiment was performed, in which the microalgae were grown in the culture supernatant, treated with ozone. The following culture treatments were carried out: control treatment, in which the lineages were cultivated in culture medium; treatments T1 and T2 in the culture supernatant; treatments T3 and T4 in the culture supernatant, after treatment with O 3 , without and with addition of nutrients; T5 and T6 treatments in the culture supernatant added with the lipid-free biomass and after treatment with O 3 , without and with addition of xinutrients; and T7 treatment in the culture supernatant, treated with activated charcoal and with added nutrients. Concentrations, in dry mass, of the cultures and the concentrations of carbohydrates, proteins and total soluble amino acids were determined. It was concluded that there was no inhibition of the cultivation in any of the treatments and that the ozone treatment of the supernatant, added with residual lipid-free biomass, presented higher dry mass concentration in the Chlorella sp. BR001 and Chlamydomonas sp. CC503. The treatments of the supernatant with ozone, added or not of defatted biomass and, added or not of nutrients, of the lineages Scenedesmus sp. BR003 and Chlamydomonas sp. CC503, presented the highest mean carbohydrate concentration. Ozone treatment of the supernatant in the three tested lineages presented the highest mean protein concentration. The treatments of the ozonated supernatant with defatted biomass, added or not of nutrients, of the lineages Scenedesmus sp. BR003 and Chlamydomonas sp. CC503, showed the highest averages of amino acid concentration. The results obtained suggest that the ozonated supernatant with lipid-free biomass and nutrient addition (T6-SOBN) presented the best averages in all analyzes, especially in the Chlamydomonas sp CC503 lineage. New studies should be conducted in order to find the best growth medium, reusing water and all compounds of interest, to optimize the cultivation of microalgae aiming at the production of biofuels.